Influência dos sistemas de produção, convencional e orgânico, na qualidade da cana-de-açúcar (Saccharum spp) e do açúcar mascavo - Minguetti, Fausto Fabrício (2012)
The brown sugar is a sweetener with nutritional characteristics, obtained directly from the concentration of sugarcane juice freshly extracted. Its production does not require usage of any chemical additives, so that it is preserved most of the original constituents of sugarcane, without any exogenous substances. This makes this product having a higher nutritional quality thau crystal sugar or refined. To evaluate the influence of fertilization, organic and conventional, in sugarcane and muscovado sugar, it was conducted an experience with six fertilization systems in randomized complete block with four replications. The canes were analyzed and later or were produced muscovado sugars that were analyzed for their physico-chemical and sensorial quality. The physico-chemical analyzes comprised the following parameters: sucrose (pol), Brix, purity, reducing sugars (AR), total reducing sugars (ART), fiber, amino acids, phenolics, potassium, pH, acidity, ash and moisture. For sensory analysis it was used the Quantitative Descriptive Analysis (QDA) by nineteen tasters. A vi preference test with 50 consumers was also performed rating a hedonic scale of 9 points. The results showed that the different fertilization systems did not influenced the physico-chemical quality of the cane. Only phenolic content showed statistical differences for different treatments. These differences, however, are very small. Regarding the physico-chemical and sensorial qualities of the sugar, despite some differences, all treatments provided sugars with good acceptance. It is noteworthy that the organic system seeks a better environmental balance bringing social and long lasting sustainable benefits.